The new face of alternative assessment in accounting sciences - technology as an anthropomorphic stakeholder - Swart, O.; Shuttleworth, C. C. (South African Journal of Higher Education, 2021)
Worldwide, more and more higher education institutions are making use of online or distance education, due to the increasing demand for tertiary education. In this article, the problem addressed relates to the importance of technology as a stakeholder in alternative assessments for undergraduate accounting sciences modules in an online, non-venue-based, technology-enhanced environment. The purpose of this article is to demonstrate how technology, due to its importance and impact, acts similarly as a human stakeholder and should be treated as an anthropomorphic stakeholder in an online technology-enhanced environment, considering its powerful role. A qualitative approach was followed, and action research was used to develop a conceptual framework. This conceptual framework demonstrates how stakeholder theory could ensure the legitimacy of qualifications through identity verification of students in an online environment through improved performance and innovation potential. These findings contribute to the body of knowledge and due to its importance, technology could be considered as an anthropomorphic stakeholder in the creation, improvement, or restructuring of assessments at online educational institutions.